2014
DOI: 10.4319/lo.2014.59.1.0195
|View full text |Cite
|
Sign up to set email alerts
|

On the phytoplankton bloom in coastal waters of southern King George Island (Antarctica) in January 2010: An exceptional feature?

Abstract: Since the early 1990s, phytoplankton has been studied and monitored in Potter Cove (PC) and Admiralty Bay (AB), King George/25 de Mayo Island (KGI), South Shetlands. Phytoplankton biomass is typically low compared to other Antarctic shelf environments, with average spring-summer values below 1 mg chlorophyll a (Chl a) m 23 . The physical conditions in the area (reduced irradiance induced by particles originated from the land, intense winds) limit the coastal productivity at KGI, as a result of shallow Sverdrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 56 publications
9
77
0
4
Order By: Relevance
“…This observation is in line with the raising summer water temperatures observed for KGI coastal waters during the last two decades (Schloss et al, 2012;Lange et al, 2014;Schloss et al, 2014). In a long-term study, Boyce et al (2010) reported that phytoplankton biomass in the global ocean, including Arctic and Antarctic regions, declined by 1%, which strongly correlates with the increase in sea surface temperatures over the past century.…”
Section: Discussionsupporting
confidence: 66%
“…This observation is in line with the raising summer water temperatures observed for KGI coastal waters during the last two decades (Schloss et al, 2012;Lange et al, 2014;Schloss et al, 2014). In a long-term study, Boyce et al (2010) reported that phytoplankton biomass in the global ocean, including Arctic and Antarctic regions, declined by 1%, which strongly correlates with the increase in sea surface temperatures over the past century.…”
Section: Discussionsupporting
confidence: 66%
“…The spatial pattern of IPAR (Figure 5b), which showed good agreement with chlorophyll-a concentration (Figure 1c), clearly illustrated the influence of light limitation on phytoplankton growth. This physical condition prevents optimal light for phytoplankton growth and this along with intense wind and terrigenous particles, typically leads to low primary productivity KGI [25]. From the perspective of this study, low light conditions ensured the reliability of the fluorescence approach and the nFLH algorithm.…”
Section: Fluorescence Approach Estimation For Chlorophyll-amentioning
confidence: 93%
“…The phytoplankton bloom reported in 2010 was dominated by micro-algae (e.g., Porosira glacialis, Thalassiosira antarctica, and T. ritscheri [25]). Phytoplankton tends to adapt their cellular physiology to optimize light harvesting and photoreception [44].…”
Section: Factors On Phytoplankton Bloom In Kgimentioning
confidence: 99%
See 2 more Smart Citations